Do Radiologists Agree on Findings in Radiographer‐Acquired Sonographic Examinations?. (1st March 2013) - Stenman, Carina; Jamil, Shazia; Thorelius, Lars; Knutsson, Anders; Smedby, Örjan
Abstract : Objectives: Sonographic examinations are usually regarded as observer dependent, but a recently introduced method using documentation with cine loops acquired in a standardized way attempts to address this problem. The aim of this study was to evaluate the intraobserver and interobserver agreement of sonographic liver examinations using strictly standardized examination protocols with cine loop documentation. Methods: Ninety‐eight outpatients were examined by a radiographer using the standardized method. Three radiologists, each with 10 to 20 years of experience in sonography, reviewed the cine loops retrospectively. After 4 weeks, the review was repeated; the 3 radiologists were blinded to the initial reading. The κ coefficient was used to analyze intraobserver and interobserver agreement, and agreement in percent was also calculated. Results: The intraobserver agreement was highest for concrements in the gallbladder (κ= 0.91–0.96) and lowest when assessing the need for further examination (κ = 0.38–0.64). For increased liver echogenicity, κ varied between 0.73 and 0.92 and for skip areas between 0.73 and 0.90. The interobserver agreement was also highest for concrements in the gallbladder (κ = 0.84–1.00) and lowest for the need for further examination (κ = −0.12–0.46). For most other findings, substantial intraobserver agreement was found. Conclusions: For sonographic examinations performed according to a standardized examination protocol by a radiographer and viewed by an experienced radiologist, good interobserver agreement was found, except for judgments of the need for further examinations.